Availability of Improved Water Sources in Public Places of Four Health Districts with Cholera History in Cameroon - TCHIO-NIGHIE, Ketina Hirma; BAYIHA, Eugene Joel; BEYALA, Landry; ATEUDJIEU, Jerome (International Journal of Innovative Research in Medical Science, 2023)
In public places as well as in homes, water is necessary for consumption, compliance with hygiene rules, sanitation and environmental cleanliness. This study describes in 2017, access to improved water sources in public places of health districts frequently affected by cholera outbreak in Cameroon. This was a cross-sectional descriptive study targeting public places in four health districts of the Littoral and Far North regions of Cameroon. Using an observational grid, data were collected on the availability of improved water sources in public places accommodating at least 100 persons daily. Public places were selected by stratified random sampling process. All 432 identified public places were included. Schools, mosques and bars were the most represented with 169 (39.1%), 74 (17.1%) and 68 (15.7%) surveyed respectively. Out of the 432 public places, 262 [60.7% (55.9-65.3)] had an improved water source. This varied with respect to types of public places and health districts. Improved water sources were available in 99 [58.6 (50.8-66.1) %] schools, 41 [55.4 (33.1-69.9) %] mosques and 46 [67.7 (55.2-78.5) %] bars. About two out of five public places were not covered by at least one point of improved water sources in 2017. Health districts more frequently affected by previous Cameroon cholera outbreak had lower coverage and schools accommodating at daily base a large number of vulnerable people need intervention.